Deposition Characteristics of Polydisperse Particles in Saturated Porous Media under Different Ionic Strengths - ZOU Zhi-ke, YU Lei, LI Ya-long, NIU Shu-yao, QIAO Wei, BIAN Jiu (长江科学院院报)
[Objectives] Polydisperse particles are widely present in natural environments. Accurately predicting the transport and deposition of polydisperse particles in saturated media under unfavorable conditions (where repulsive forces exist between particle and medium surfaces) is crucial. [Methods] A series of constant-flow one-dimensional sand column experiments with artificial recharge were conducted using polydisperse particles (0.375-18.863 μm) under different ionic strength conditions (1, 6, 20, and 200 mM). Deposition characteristics of polydisperse particles under different ionic strengths (unfavorable and favorable conditions) were investigated. By coupling the colloid attachment efficiency model under unfavorable conditions with the polydisperse particle deposition model, a deposition model for polydisperse particles under unfavorable conditions was established, and corresponding numerical simulations were performed. [Results] Both physical experiments and numerical simulations showed that under favorable conditions, the capture probability of polydisperse particles exhibited a non-monotonic V-shaped characteristic of first decreasing and then increasing with particle size due to uneven micro-force distribution. Compared with favorable conditions, the repulsive double-layer force between polydisperse particles and the medium surface under unfavorable conditions formed an energy barrier, leading to an 8.5%-67.6% reduction in capture probability. The smaller the particle size, the greater the reduction in particle capture probability. Under favorable conditions, the final deposition profile curve of particles exhibited a hyper-exponential distribution with “upper-steep, lower-gentle”. The total deposition amount increased with increasing ionic strength, with 16.7%-24.6% of the total deposition occurring in the upper part of the sand column. A decrease in ionic strength exacerbated the uneven “upper-steep, lower-gentle” distribution of the deposition profile. [Conclusions] The research results not only further reveal the transport and deposition characteristics of polydisperse particles under natural unfavorable conditions, but also provide a scientific basis for effective watershed water quality management.